2013
DOI: 10.1371/journal.pone.0075078
|View full text |Cite
|
Sign up to set email alerts
|

Different Traits Determine Introduction, Naturalization and Invasion Success In Woody Plants: Proteaceae as a Test Case

Abstract: A major aim of invasion ecology is to identify characteristics of successful invaders. However, most plant groups studied in detail (e.g. pines and acacias) have a high percentage of invasive taxa. Here we examine the global introduction history and invasion ecology of Proteaceae—a large plant family with many taxa that have been widely disseminated by humans, but with few known invaders. To do this we compiled a global list of species and used boosted regression tree models to assess which factors are importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 48 publications
4
84
0
Order By: Relevance
“…For example, there was a positive significant effect of the number of leaves on the survival probability of I. carnea in wastelands, whereas survival probability decreased significantly with increasing leaf biomass in canal banks and wastelands habitat. Moodley et al (2013) stated that for some plant traits there are clear mechanisms for the association of selected traits and invasion success, also some traits show differing responses at the different stages of invasion. Leaf traits in particular have been linked to invader success, including a large meta-analysis of local and global leaf traits predicting invasion (Leishman et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, there was a positive significant effect of the number of leaves on the survival probability of I. carnea in wastelands, whereas survival probability decreased significantly with increasing leaf biomass in canal banks and wastelands habitat. Moodley et al (2013) stated that for some plant traits there are clear mechanisms for the association of selected traits and invasion success, also some traits show differing responses at the different stages of invasion. Leaf traits in particular have been linked to invader success, including a large meta-analysis of local and global leaf traits predicting invasion (Leishman et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The few studies that empirically tested for traits associated with different transitions indeed found that different traits may be important at the different stages (van Kleunen et al 2007;Dawson et al 2009;Pysek et al 2009) or even that certain traits may have opposing effects at different transitions. For example, Moodley et al (2013) found for the Proteaceae family that large seeds promoted naturalization but that small seeds promote invasion. Although the introduction naturalization invasion framework is very useful, it is only applicable at the larger regional scale (for which species can be classified as introduced, naturalized or invasive), which hampers the inclusion of the local-community context.…”
Section: Introductionmentioning
confidence: 99%
“…An additional complication is that effects can be in different directions, e.g. a trait might increase the chance of a species being introduced but reduce the chance of an introduced species becoming invasive (Moodley et al 2013).…”
Section: Introductionmentioning
confidence: 99%